C. elegans spermatozoa lacking spe-45 are incapable of fusing with the oocyte plasma membrane - Takayama, Jun (MicroPubl Biol, 2021)
C. elegans spe-9 class genes encode sperm proteins with indispensable roles during fertilization. We have previously reported that spe-45 belongs to the spe-9 class, based on the finding that self-sperm of spe-45(tm3715) hermaphrodites were not consumed by fertilization. In this study, we directly observed live fertilization in the spermatheca of fem-1(hc17) females after mating with spe-45(tm3715) males. As expected, it was clearly shown that spe-45 mutant spermatozoa failed to fuse with the oocyte plasma membrane. Thus, our live imaging system for C. elegans fertilization seems to be useful for evaluation of the functions of male and female gametes.